2007
DOI: 10.3989/redc.2007.v30.i2.378
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration in science among Latin American countries

Abstract: Resumen: Un análisis de la colaboración científica entre los países de Amé-rica Latina a través de documentos registrados de 1975-2004 en el Science Citation Index versión Web of Science, revela un aumento paulatino en el número total de trabajos principalmente en la última década, así como en los porcentajes de éstos del total de publicaciones registradas por la región. La magnitud de estos aumentos varía; los países más pequeños mostraron los niveles más altos de colaboración, en especial aquellas colaborac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 5 publications
0
3
0
3
Order By: Relevance
“…Additionally, opinion pieces from Latin-American researchers also agree about the linguistic barrier in science [ 39 , 57 ]. It is possible to assume that these results can be extrapolated to other countries bordering Colombia, given the similarity in proficiency and access to English, shared first language, low state investment in science and technology, and parallel political history with the US and Europe [ 11 , 58 , 59 ]. The results could even be extrapolated to other peripheral countries of the world, as Hanauer et al [ 12 ] found similar disadvantages over doctoral students from two countries on different continents, Mexico, and Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, opinion pieces from Latin-American researchers also agree about the linguistic barrier in science [ 39 , 57 ]. It is possible to assume that these results can be extrapolated to other countries bordering Colombia, given the similarity in proficiency and access to English, shared first language, low state investment in science and technology, and parallel political history with the US and Europe [ 11 , 58 , 59 ]. The results could even be extrapolated to other peripheral countries of the world, as Hanauer et al [ 12 ] found similar disadvantages over doctoral students from two countries on different continents, Mexico, and Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…It was expected that additional costs for Colombian researchers would be found, since similar findings have been reported from other EFL speaking countries in the world (McConnell, 1991; Flowerdew, 2007; Nour, 2005; Guardiano et al, 2007; Curry & Lillis, 2017; Hanauer et al, 2019). Despite the lack of specific studies on this subject across Latin America, with a few exceptions (Curry & Lillis, 2017; Hanauer et al, 2019), it is possible to assume that these results can be extrapolated to other countries bordering Colombia, given the similarity in proficiency and access to English, shared first language, low state investment in science and technology, and parallel political history with the US and Europe (Russell et al, 2008; British Council, 2015; Curry & Lillis, 2017). The results could even be extrapolated to other peripheral countries of the world, as Hanauer et al (2019) found the similar disadvantages over doctoral students from two countries on different continents, Mexico and Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…En el año 2007 se realizó una investigación que tenía como propósito definir el índice de publicaciones y producción científica en América Latina en los períodos de 1975 a 2004 en la Web of Science, En los resultados se determina un aumento del número total de trabajos en la región, siendo la colaboración Brasil-Argentina quien domina las colaboraciones bilaterales intra-regionales. Los autores llegan a la conclusión de que los índices de producción científica a nivel Latinoamericano se encuentran en constante ascenso y cobra impulso debido a las tendencias que existen a nivel mundial (Russell et. al, 2007).…”
Section: Trabajos Relacionadosunclassified